Implementation of Working Agreement with Probationary Period in Financial Industry According to Labor Law - Johan, Suwinto (SASI, 2022)
Introduction: This study looks at how to implement a three-month probationary period for probationary employees.Purposes of the Research: The purpose of this study is to examine the working interaction between employees and employers in the financial industry during a employment agreement with a probationary period.Methods of the Research: This study employs a normative legal research approach.Results of the Research: The findings of this study show that a three-month probationary period is insufficient for evaluating a worker's performance. The extension of a probationary period for a worker is prohibited by law. Companies must look for new ways to appraise employee. Probationary periods are more suited to non-management positions than to managerial positions. For managerial level, the probationary term is more than three months. The level of directors is not regulated under labor laws. Labor law does not need to govern work agreements for workers at the managerial level. The parties' agreement can be regulated by the civil law.